Establishment of a dual droplet digital PCR method for detecting the Brucella abortus A19-ΔVirB12 strains - Xue, Ruixue; Chu, Zunfeng; Xing, Linlin; Jiang, Zixin; Jiang, Wenduo; Shang, Yingli; Wang, Fangkun; Wang, Hongmei; Zhang, Yuyu; Wang, Yanling; Miao, Yu; Zhang, Xinglin; et al. (Frontiers in Microbiology, 2025)
Brucellosis is a zoonosis that occurs worldwide, and vaccination is the main strategy for controlling it. In China, the Brucella abortus A19-ΔVirB12 strain is utilized in main vaccines. However, a high-sensitivity nucleic acid detection method to effectively differentiate Brucella infections from immunization with the A19-ΔVirB12 strain is lacking. Therefore, in this study, a duplex droplet digital PCR (ddPCR) assay was established using primers and probes targeting the VirB8 gene and the deleted VirB12 gene in the A19-ΔVirB12 strain. The specificity of the method was tested using genomic DNA of Mycobacterium bovis, Escherichia coli (O:157), Salmonella spp., Streptococcus spp., and A19-ΔVirB12 Brucella. Only A19-ΔVirB12 amplified VirB8 gene. The detection limits of the method for VirB8 and VirB12 were 2.13 × 100 and 2.26 × 100 copies/μL, respectively. In the detection of DNA in epidemic-related samples, the positive rate of ddPCR was much higher than that in the samples analyzed using the commercial fluorescence quantitative reagent kits. Meanwhile, the ddPCR of the A19-ΔVirB12 Brucella vaccine strain was identified in the clinical samples. In summary, the ddPCR method with high sensitivity and specificity was established, which will support the future identification of A19-ΔVirB12 Brucella vaccine strains in immunized and wild-type Brucella.